Frequency Characteristics of Resistance Metering Units Operating Aigorithms in Overhead Lines Digital Distance Protection Devices - V. I. Novash; V. V. Shmyhin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper describes the frequency characteristics of the most commonly used algorithms of digital resistance metering units in up to date distance protection devices. The evaluation of the application cases of different algorithms was performed, also the comparative analysis of the calculated resistance accuracy under frequency deviation conditions according to the algorithms being considered quoted.